3x-42=2(x-13)

Simple and best practice solution for 3x-42=2(x-13) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x-42=2(x-13) equation:



3x-42=2(x-13)
We move all terms to the left:
3x-42-(2(x-13))=0
We calculate terms in parentheses: -(2(x-13)), so:
2(x-13)
We multiply parentheses
2x-26
Back to the equation:
-(2x-26)
We get rid of parentheses
3x-2x+26-42=0
We add all the numbers together, and all the variables
x-16=0
We move all terms containing x to the left, all other terms to the right
x=16

See similar equations:

| 6(1-4x)=30-6x | | 7x+27=79 | | 5x+6/6=2x-2 | | −7x−13=8 | | 40h=240 | | -3(x+7)=-15 | | m^2+7m+17=5 | | 57+8x=169-6x | | 2/3y-3/2=8/7 | | 15=5/2w | | 5(2x-5)=2x+47 | | w/5+5=10 | | 5x-(12)=-7 | | 2x+21-7=50 | | x-(.3x)=45 | | x^2+9x+2=-20 | | X-5x=-44 | | -25-3x=5 | | 3x+3-18+x=-30+60 | | 7-14=18-4x | | -4x+10=2x-3 | | t÷3-4=11 | | 46+3x+13=8x-1 | | 8y-10y=-8-12 | | -w/7=-24 | | 10x=2x×5 | | 159-y=219 | | 2x+66=-24 | | 5.15x+6=72.95 | | 10x=2x+2 | | 9h−10=26 | | (x)+7=5 |

Equations solver categories